Types of Conduct under Open and Hidden Impact - V P Sheinov (Peoples' Friendship University of Russia (RUDN University), 2015)
The article justifies the inclusion of the manipulative behavior in the classical typology of behavior (passive, aggressive, assertive). It is shown that all the four types of behavior have fundamentally different models of the psychological influences and transactions realizing them.